PENERAPAN POLA ASUH OLEH ORANG TUA TUNGGAL (IBU) DALAM PENCAPAIAN PENDIDIKAN FORMAL ANAK - Fitri, Eliza Riani; Rustiyarso, Rustiyarso; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was  to know about application of parenting by single parents (mother) in terms of achievement of formal education. . The techniques of data collection were observation, interview and the study of documentation, where as the tools of data collection were the directive of observation, directive of interview, the notes and the files like report, trophy, and certificate. This research sources were primer data and secodary data. The result of this research proves that single parents (mother) apply different parenting patterns. usually, job is single parents? (mother) first priority that makes them lose the oppurtunity to pay attention to the child?s behavior and education at school. Furthermore, because the exhausting job, single parents tend to speak abusively, do a violent action especially when they command the child to prepare their school, homework, and difficulty to facilitate school instruments and transportation. Because of the frequency of single parents (mother) existence is low, children tend to play all day without parents? control. This problem makes children couldn?t feel the attendance of parents to give them love and affection. Also, children has so many lack in getting education both at school and at home, low academic grades, quit school before graduating, not even get on the next grade. Keywords : Parenting, Single Parents (Mother), Achievement Formal Education